Vietnam : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
Vietnam was remarkably successful in bringing down inflation in the 1990s to a single-digit range, after a period of high inflation in the late 1980s. The potential unfavorable effects of inflation on poverty and growth are well known. To shed light on these questions, this paper analyzes the available empirical evidence using several different approaches. Petroleum price increases appear to have had a modest direct effect on inflation in Vietnam, peaking at about 1 percent in 2005.